2020
DOI: 10.1029/2020gl088930
|View full text |Cite
|
Sign up to set email alerts
|

The Boundary of Alkali Surface Boundary Exospheres of Mercury and the Moon

Abstract: Global exosphere models of alkali gases surrounding Mercury and the Moon assume that the primary effect of the porous soil is to reduce the effective desorption rates. We demonstrate with a kinetic simulation that, following adsorption, the complicated structure of soils has two additional effects on the fate of previously released alkali atoms: (1) trapping of free atoms at lunar temperatures by microscopic shadows and inward diffusion, which becomes the primary sink mechanism, and (2) high‐energy barriers fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Still, kinetic models in Fig. 4 Sarantos and Tsavachidis 2020) demonstrate that this geometric effect is only a partial explanation of the observed linewidth enhancement and consequently the Moon's exosphere is hotter at New Moon phases. concluded that the largest measured scale heights are at dawn and dusk, and are correlated with local solar time.…”
Section: Used Anmentioning
confidence: 92%
See 1 more Smart Citation
“…Still, kinetic models in Fig. 4 Sarantos and Tsavachidis 2020) demonstrate that this geometric effect is only a partial explanation of the observed linewidth enhancement and consequently the Moon's exosphere is hotter at New Moon phases. concluded that the largest measured scale heights are at dawn and dusk, and are correlated with local solar time.…”
Section: Used Anmentioning
confidence: 92%
“…Our inability to explain the observed Na cycle suggests that current models of the surfaceexosphere interaction may be incomplete. Some progress towards a better specification of the boundary conditions for models was contained in the recent work of Sarantos and Tsavachidis (2020). To understand how the microstructure of soil affects the exospheric reservoir for alkalis, a simulation of a porous soil (1 mm in depth) was produced in that work using spherical grains sampled with a distribution of grain sizes from Apollo Lunar Soil Sample 72141, a typical mature soil (keeping in mind that Mercury's regolith is probably different from Moon's regolith, as an example, in composition).…”
Section: The Role Of the Surface Interaction With The Exospherementioning
confidence: 99%
“…When a particle was determined to stick to the surface, no subsequent desorption events were considered. It has been suggested that ∼60% of Na atoms that stick to the lunar regolith are lost to microscopic shadows on each bounce (Sarantos & Tsavachidis 2020). The model assumed that the Na source rate near the subsolar point is ∼2 × 10 6 Na atoms cm −2 s −1 (Sarantos et al 2010).…”
Section: Constraints On Exospheric Structurementioning
confidence: 99%
“…Recent works have illustrated the need for more accurate simulations of the surfaceexosphere interaction in airless bodies. For example, Sarantos and Tsavachidis (2020) showed that the mobility of alkalis (Na and K) on the surface of regolith grains on both the Moon and Mercury reduce the overall desorption of these species from these grains. On the Moon, this effect might explain why the sodium exosphere reacts more slowly to the changes of the micrometeoroid flux compared to potassium, because the latter, being more massive than the former, has an overall reduced surface mobility, and therefore a higher chance to be photodesorbed.…”
Section: Simulationsmentioning
confidence: 99%